THE RUSSIAN VECTOR IN TURKMENISTAN’S FOREIGN POLICY - ŠÍR, Jan (CENTRAL ASIA AND THE CAUCASUS, 2006)
By keeping away from practically all mechanisms of regional integration and cooperation, Turkmenistan stands apart from its Central Asian neighbors. One of the CIS founding members, it gradually reduced its involvement in the Commonwealth to purely nominal: nowadays the CIS is regarded as a structure that passes general non-obligatory decisions, while the U.N.s declared to be the republic’s priority for ideo-logical reasons. At the same time, the very specific nature of Turkmenistan’s ruling regime is keeping the world community away from the country’s domestic affairs. For the same reason, Turkmenistan refused to grasp the opportunity offered by the events of 9/11, which riveted the world’s attention on the region, to extend its ties with the West, something that other Central Asian countries did not miss. On the whole, Turkmenistan can be described as a closed country devoid of any geopolitical ambitions, opting for voluntary self-isolation. Inside the country, this is de-scribed as “positive neutrality.” The constitutional Law on Turkmenistan’s Permanent Neutrality of 27 December 1995 serves as the legal cornerstone of the country’s foreign policy. It describes Turkmenistan’s Constitution, rights, and obligations as those of a neutral state. In the military-political sphere, in particular, it is expected to pursue a peace-loving foreign policy based on the principles of equality, mutual respect, and non-interference in the domestic affairs of other states and keep away from military blocs, unions, and inter-state alliances that impose strict functions on or presup-pose collective responsibility of its members under the law, the republic pledges not to start wars and armed conflicts, not to take part in them (self-defense being the only exception), and not to do anything that might provoke a war or a conflict. The country does not allow other states to set up military bases on its territory or use its territory for military purposes, nor does it possess, produce, or take part in the proliferation of weapons of mass destruction. In the economic sphere, the republic is expected to develop international mutually advantageous economic cooperation on the basis of equality and with due account of the interests of all the sides involved; to keep open its financial-economic expanse; and to avoid eco-nomic pressure as a political tool (the “open doors” strategy is a foreign economic component of the “positive neutrality” conception). Finally, in the humanitarian sphere, the republic pledges to recognize and respect the basic generally accepted human and civil rights and democratic freedoms; to promote international exchange of spiritual values; and to cooperate with the world community on the humanitarian issues.1 Certain Turkmenia lawyers insist that besides being set forth in the country’s domestic legislation, their country’s neutral status rests on the firm basis of international law.2 This sounds like an overstatement: the problem belongs primarily to the con-text of nation-building and the development of Turkmenistan’s national ideology. For historical reasons, more equal relationships with the former Center remain a priority at the level of bilateral relations. On 8 April 1992, Turkmenistan and the Russian Federation established diplomatic relations, the main principles of which were consolidated in the Treaty on Friendship and Cooperation of 31 July 1992. The document envisaged the need for close interaction in the foreign policy and defense spheres while pre-serving a common military-strategic expanse and including mutual assistance in the event of aggression against one of the sides. Equal and mutually advantageous economic cooperation was also envisaged to create a free trade area, customs union, and common economic expanse as well as cooperation on a wide range of humanitarian is-sues, including the guarantee of basic human rights and the rights of national minorities.3 In practice, however, the desired level of communications has not been achieved in any of the spheres. On 23 April, 2002, as a result of Presi-dent Putin’s visit to Turkmenistan, the two countries signed a new basic treaty that envisaged few-er mutual rights and obligations of the sides.4 The vague wording of the new document not with-standing, it much more adequately reflects the present level of relations as well as the fundamental changes that have recently taken place in the relations between the two countries.